THE IMPORTANCE OF APPLYING AND DEVELOPING CRITICAL THINKING IN ACCOUNTANTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines what critical thinking is and why critical thinking has become especially important for accountants in the context of digitalization. Critical thinking is not just a skill, but a necessary competence that allows an individual to successfully adapt to the rapidly changing world and make informed decisions in everyday life. The integration of critical thinking into educational programs will create the foundation for the formation of a responsible and conscious citizen who can actively participate in the life of society and contribute to its development.